2021
DOI: 10.3389/fnhum.2021.689912
|View full text |Cite
|
Sign up to set email alerts
|

Visual Neuropsychology in Development: Anatomo-Functional Brain Mechanisms of Action/Perception Binding in Health and Disease

Abstract: Vision is the main entrance for environmental input to the human brain. Even if vision is our most used sensory modality, its importance is not limited to environmental exploration. Rather it has strong links to motor competences, further extending to cognitive and social aspects of human life. These multifaceted relationships are particularly important in developmental age and become dramatically evident in presence of complex deficits originating from visual aberrancies. The present review summarizes the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 305 publications
(323 reference statements)
2
13
0
Order By: Relevance
“…Linking the present study to some basic findings concerning brain development (e.g., [29]), there is a brain area for processing face-like stimuli (the fusiform face area) which appears to help infants as young as 4 months old to process faces, and which appears to continue to develop during childhood. Given these general facts, it seems likely that this FFA guided our preschool children's attention to the agent's head/face during our study.…”
Section: Discussionsupporting
confidence: 66%
“…Linking the present study to some basic findings concerning brain development (e.g., [29]), there is a brain area for processing face-like stimuli (the fusiform face area) which appears to help infants as young as 4 months old to process faces, and which appears to continue to develop during childhood. Given these general facts, it seems likely that this FFA guided our preschool children's attention to the agent's head/face during our study.…”
Section: Discussionsupporting
confidence: 66%
“…These findings were echoed by Provazza and colleagues demonstrating a similar visual processing challenge in this population (Provazza et al, 2019). Considering the brain networks involved, for example, in visuospatial processing (Perruchoud et al, 2016) or attention (Pamplona et al, 2020) comprise a large number of brain regions and related interconnections both in adulthood and development (Ionta, 2021), it is possible that in individuals with dyslexia, possibly over time/age, natural neuroplastic compensatory mechanisms are put in place to establish alternative neural activations/connections which would make dyslectic people able to compensate their deficits and resemble the performance of their age-matched non-dyslectic peers in the domains of organization, visual-spatial abilities, shifting, and attention. Despite the great benefit behavioral and cognitive testing provide when discussing reading and EF abilities in those with dyslexia, one limitation of behavioral tests is that they can be considered versatile in the functions they assess.…”
Section: Adults With Dyslexia (22+)mentioning
confidence: 78%
“…Furthermore, the present investigation revealed an interhemispheric pattern of asymmetric transfer, encompassing the parietal and frontal regions, as depicted in Figure 2 . While the changes in the processing of the visual cortex are commonly implicated in reading proficiency [ 50 , 51 , 52 ], recent studies have indicated that the development of reading is also associated with the maturation of brain regions beyond the visual cortex [ 53 ]. Specifically, Ionta (2021) conducted a comprehensive review of previous neuropsychological evidence [ 53 ], highlighting the importance of visuo–motor integration skills and proposing that reading development may induce neurally based alterations in brain areas other than the visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…While the changes in the processing of the visual cortex are commonly implicated in reading proficiency [ 50 , 51 , 52 ], recent studies have indicated that the development of reading is also associated with the maturation of brain regions beyond the visual cortex [ 53 ]. Specifically, Ionta (2021) conducted a comprehensive review of previous neuropsychological evidence [ 53 ], highlighting the importance of visuo–motor integration skills and proposing that reading development may induce neurally based alterations in brain areas other than the visual cortex. Previous research has presented a visual neuropsychological model that explains two main streams [ 53 , 54 ], the “what” pathway in the ventral stream and the “where” pathway in the dorsal stream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation